Clinical evaluation of the i-gel Plus supraglottic airway in Japanese patients: A prospective observational study - Toshiyuki Nakanishi; Ayaka Tani; Kei Matsumoto; Atsushi Ishikawa; Yuki Takami; Yuji Kamimura; Rina Kato; MinHye So; Kazuya Sobue (PLoS ONE, 2026)
Background The i-gel® Plus, a new supraglottic airway, has a high oropharyngeal leak pressure of 32 ± 7 cmH 2 O in the European population. Because the i-gel® series was developed based on the laryngeal anatomy in Western populations, its performance in other regions, such as East Asia, is unknown. Therefore, we aimed to perform an initial clinical evaluation of i-gel® Plus in Japanese patients. Methods This prospective observational study, conducted from March to June 2024 at a university hospital in Japan, recruited a total of 64 adult patients, 16 each of nonelderly (18–69 years) male, nonelderly female, elderly (≥ 70 years) male, and elderly female patients. Patients with a suspected high risk of aspiration or a predicted difficult airway were excluded. We recorded the oropharyngeal leak pressure (primary outcome), first-attempt success rate, and fiberoptic views of the i-gel® Plus. Continuous variables were evaluated for normality using the Shapiro–Wilk test and Q-Q plot. The groups were stratified by age and sex for exploratory analysis. Results Of the 67 enrolled patients, three were excluded: one 70-year-old male because of failed ventilation and two because of missing data. Finally, 64 patients were analyzed, with 16 patients in each age-sex group. The oropharyngeal leak pressure was 23.7 ± 6.9 (mean ± standard deviation) cmH 2 O, which was normally distributed based on the Shapiro–Wilk normality test (P = 0.593) and Q-Q plot. The first-attempt success rate was 92% (including one failed ventilation case), and visible vocal cords were observed in 80% of cases. In exploratory comparisons by sex, male patients had lower oropharyngeal leak pressure and fewer visible vocal cords than female patients. Conclusions The i-gel® Plus showed a high first-attempt success rate of 92%; however, its oropharyngeal leak pressure was lower than expected at 23.7 ± 6.9 cmH 2 O in this Japanese cohort.